Idiopathic Gingival Enlargement and its Management: A Case Report: - Manoj Kumar1, Amit Kumar Srivastava2, Lora Mishra3, Rinkee Mohanty4, Saurav Panda1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Idiopathic gingival overgrowth is an unusual condition that leads to a gigantic overgrowth of the gumswithout any specific etiology. The enlargement leads to multiple issues and makes chewing difficult forthe patient along with the unsightly appearance. Here we present a case of idiopathic gingival enlargementwithout any syndromic association in a 45- year old female patient. It was managed by surgical treatmentincluding gingivectomy followed by gingivoplasty and was monitored regularly due to its high rate ofrecurrence.